Female Personality in Andrea Hirata’s Novel Sirkus Pohon - ., Asnani; Siregar, A; Hariani, S; ., Pardi (KnE Social Sciences, 2018)
The research aims to figure out the female personality in Andrea Hirata’s novel Sirkus Pohon. The female personality in the novel is quite interesting to be discussed because in this novel, Andrea Hirata makes us laugh following the innocent female Malay personality in the Belitong countryside, sobbing by the sad love story, or shaking their heads by their tremendous intrigues. We will find imperfect humans, but at the same time find wisdom through their personality. Hirata has portrayed female personality in the novel through five females, namely: Tara, Dinda, Azizah, Tara’s mother and Tegar’s mother. According to Maslow (2002) personality is a pattern of behavior and habits of human. Smith (2004) states that personality is patterned of habits, traits, attitudes, and ideas of an individual. The writers discuss female personality through the personality of Tara, Tara’s mother, Dinda, Azizah, and Tegar’s mother. It is discussed in the analysis. The research uses qualitative research in description analysis by quoting some sentences related to the analysis. The results of the research are: Tara’s personalities are faithful and fragrant; Dinda’s personalities are having a soft heart and losing her memory; Azizah’s personality is chatty but loving her family; Tara’s mother’s personalities are beautiful, kindness, smart and strong; and Tegar’s mother is weak and a heartbroken woman. Keywords: female, personality, faithful, soft-heart, quarrelsome, strong, weak